2020
DOI: 10.1161/strokeaha.120.029734
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Door-to-Needle Improvement Initiative Results in Improved Patient Outcomes Across an Entire Population

Abstract: Background and Purpose: Improving door-to-needle times (DNTs) for thrombolysis of acute ischemic stroke patients improves outcomes, but participation in DNT improvement initiatives has been mostly limited to larger, academic medical centers with an existing interest in stroke quality improvement. It is not known whether quality improvement initiatives can improve DNT at a population level, including smaller community hospitals. This study aims to determine the effect of a provincial improvement col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…Additionally, this study shows that access to rapid imaging interpretation from radiology is also a barrier. This urban-rural disparity in stroke treatment is consistent with previous quantitative studies that showed that rural AIS patients are less likely to receive thrombolysis (27) and have longer DTN times (14) than their urban counterparts. This disparity is apparent despite the use of tPA in AIS patients being reported as successful in rural settings, or in areas where access to a neurologist and imaging expertise is limited (28).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, this study shows that access to rapid imaging interpretation from radiology is also a barrier. This urban-rural disparity in stroke treatment is consistent with previous quantitative studies that showed that rural AIS patients are less likely to receive thrombolysis (27) and have longer DTN times (14) than their urban counterparts. This disparity is apparent despite the use of tPA in AIS patients being reported as successful in rural settings, or in areas where access to a neurologist and imaging expertise is limited (28).…”
Section: Discussionsupporting
confidence: 88%
“…Acute stroke management practices in rural areas have been labeled as sub-optimal, resulting in a gap in quality of treatment in urban and rural areas (13). A recent study that reduced DTN times across an entire population showed that urban and community hospitals with access to neurologists at all times were able to reduce their median DTN times to 35 and 34 min from 65 to 73 min, respectively, but rural hospitals were only able to reduce their DTN times to a median of 54 min from 84 min (14). There is a need to better understand the barriers to fast treatment in rural hospitals to ensure equitable care.…”
Section: Introductionmentioning
confidence: 99%
“…While outcomes data was not collected in this study, prior work has shown that a province wide reduction in DTN time of 31 min (median) lead to an increased percentage of patients discharged home from acute care, a reduction in in-hospital mortality, and a 10-day increase in 90-day hometime (the number of days a patient spends at home in the first 90 after stroke). 25 …”
Section: Discussionmentioning
confidence: 99%
“…While outcomes data was not collected in this study, prior work has shown that a province wide reduction in DTN time of 31 min (median) lead to an increased percentage of patients discharged home from acute care, a reduction in in-hospital mortality, and a 10-day increase in 90-day hometime (the number of days a patient spends at home in the first 90 after stroke). 25 Individual DTN targets were different for rural and urban centres. The target for urban centres was 30 min based on the target median from the Canadian Best Practice Guidelines and the target for rural centres was 60 min (based on the 90th percentile target from the Canadian Best Practice Guidelines).…”
Section: Discussionmentioning
confidence: 99%
“…Improvement Collaborative Intervention thrombolysis to 15.7% from 9.3%, and an additional 13% of patients that received thrombolysis were able to return home from acute care. 39 Based on the experiences in Alberta, 36 the Improvement Collaborative intervention will be modified to be more effective and efficient. Figure 1 shows the overall Improvement Collaborative intervention that will be used for this project.…”
Section: The Intervention Will Increase the Proportion Of Ischemic Stmentioning
confidence: 99%